2013
DOI: 10.2478/v10247-012-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Using the ARP-03 for high-resolution mapping of calcic horizons

Abstract: A b s t r a c t. The aim of this work is to present a fast and cheap method for high-resolution mapping of calcic horizons in vineyards based on geoelectrical proximal sensing. The study area, 45 ha located in southern Sicily (Italy), was characterized by an old, partially dismantled marine terrace and soils with a calcic horizon at different depths. The geoelectrical investigation consisted of a survey of the soil electrical resistivity recorded with the Automatic Resistivity Profiling-03 sensor. The electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Root counts (RC) below 1.2 m also differed between profiles ( Figure 1C ments), might have constituted an impenetrable layer for roots. ER sensitivity to the presence of hardpan was also reported by other authors (Tabbagh et al, 2000;Priori and Fantappi, 2013). As mentioned, a petrocalcic horizon of high resistivity was also found in trench A4 (ER=56.4 Ohm m); this area however is situated at the bottom of the field where drainage channels converge (at the time of measurements below 1.20 m there was a water content of 22%).…”
Section: Resultssupporting
confidence: 81%
“…Root counts (RC) below 1.2 m also differed between profiles ( Figure 1C ments), might have constituted an impenetrable layer for roots. ER sensitivity to the presence of hardpan was also reported by other authors (Tabbagh et al, 2000;Priori and Fantappi, 2013). As mentioned, a petrocalcic horizon of high resistivity was also found in trench A4 (ER=56.4 Ohm m); this area however is situated at the bottom of the field where drainage channels converge (at the time of measurements below 1.20 m there was a water content of 22%).…”
Section: Resultssupporting
confidence: 81%
“…For fine scale mapping, proximal sensing of the soil's electrical conductivity appears to be an efficient way to map calcic horizons (Priori et al ., ). Priori et al .…”
Section: Mapping Soil Profiles and Pedological Featuresmentioning
confidence: 97%
“…Priori et al . () concluded that the depth to the calcic horizon in a vineyard showed a strong correlation with soil electrical conductivity by combining data from the geoelectrical sensor with a limited number of soil cores.…”
Section: Mapping Soil Profiles and Pedological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…EMI measurements are also influenced by the gravel content [16], soil depth [17], bulk density [18] and, indirectly, soil water availability [19]. The correlation between ER and soil water retention can be explained by the strong relationships of both variables with soil physical features, like texture, coarse fragments, and porosity [20].…”
mentioning
confidence: 99%